Peripheral nerves adjacent to spinal cord injury could help restore sensory motor regeneration in complete paralysis patients - Mohammad Mousazadeh (Romanian Neurosurgery)
Peripheral nerves adjacent to spinal cord injury could help restore sensory motor neurons regeneration